Effects of multilevel surgery on a flexed knee gait in adults with cerebral palsy - Putz, Cornelia; Wolf, Sebastian Immanuel; Gernand, Eva-Maria; Geisbüsch, Andreas; Gantz, Simone; Dreher, Thomas (The bone & joint journal, 2017)
AimsA flexed knee gait is common in patients with bilateral spastic cerebral palsy and occurs with increased age. There is a risk for the recurrence of a flexed knee gait when treated in childhood, and the aim of this study was to investigate whether multilevel procedures might also be undertaken in adulthood.Patients and MethodsAt a mean of 22.9 months (standard deviation 12.9), after single event multi level surgery, 3D gait analysis was undertaken pre- and post-operatively for 37 adult patients with bilateral cerebral palsy and a fixed knee gait.ResultsThere was a significant improvement of indices and clinical and kinematic parameters including extension of the hip and knee, reduction of knee flexion at initial contact, reduction of minimum and mean knee flexion in the stance phase of gait, improved range of movement of the knee and a reduction of mean flexion of the hip in the stance phase. Genu recurvatum occurred in two patients (n = 3 legs, 4%) and an increase of pelvic tilt (> 5°) was found in 12 patients (n = 23 legs, 31%).ConclusionAdult patients with bilateral cerebral palsy and a flexed knee gait benefit from multilevel surgery including hamstring lengthening. The risk of the occurence of genu recurvatum and increased pelvic tilt is lower than has been previously reported in children.Cite this article: Bone Joint J 2017;99-B:1256-64.